Extensive Growth of an Anaplastic Meningioma - Hajrullah Ahmeti; Homajoun Maslehaty; Athanasios K. Petridis; Alexandros Doukas; Mehran Mahvash; Harald Barth; H. M. Mehdorn (Case Reports in Neurological Medicine)
We present the case of a 30-year-old male patient with an almost complete destruction of the calvarial bone through an anaplastic meningioma diagnosed in line with dizziness. Neuroimaging revealed an extensive growing, contrast enhancing lesion expanding at the supra- and infratentorial convexity, infiltrating and destroying large parts of the skull, and infiltrating the skin. Due to progressive ataxia and dysarthria with proven tumor growth in the posterior fossa in the continuing course, parts of the tumor were resected. A surgical procedure with the aim of complete tumor resection in a curative manner was not possible. Six months after the first operation, due to a new tumor progression, most extensive tumor resection was performed. Due to the aggressive and destructive growth with a high rate of recurrence and tendency of metastases, anaplastic meningiomas can be termed as malignant tumors. The extrinsic growth masks the tumor until they reach a size, which makes these tumors almost unresectable. In the best case scenarios, the five-year survival is about 50%. With the presented case, we would like to show the aggressive behavior of anaplastic meningiomas in a very illustrative way. Chemotherapy, radiotherapy, and surgery reach their limits in this tumor entity.